Perbandingan Desain Dermaga Terapung Pada Sistem Konstruksi Melintang dan Memanjang “Studi Kasus Dermaga Pelabuhan Tideng Pale Kabupaten Tana Tidung” - Edy Utomo (Borneo Engineering : Jurnal Teknik Sipil, 2018)
Floating port is a barge made of rectangular steel or concrete that can float to adjust the water lavel. Barge is a cargo ship type do not have a propulsion system. So, design of floating port preferably aqual to ship design. There are 3 types of barge construction system, that are longitudinal system, transversal system and mixed construction. To get the optimal design of floating port, comparison of design based on the construction system is needed. Case study in this research ia a Tideng Pale-KTT floating port. Deformation and stress analysis using FEA method on 2 models of construction system, that are transversal and longitudinal. Based on results, both of construction system produce a good strength value. However, there are some construction component which does not match the placement of the construction system. Results of construction costs have 5,51% deviation, longitudinal sytem is more expensive. So, produce the hypotheses to do a combination for both of construction systems.